Financial Impact of Liver Sharing and Organ Procurement Organizations' Experience With Share 35: Implications for National Broader Sharing. Issue 1 (15th September 2015) - Fernandez, H.; Weber, J.; Barnes, K.; Wright, L.; Levy, M.
Abstract : The Share 35 policy for organ allocation, which was adopted in June 2013, allocates livers regionally for candidates with Model for End‐Stage Liver Disease scores of 35 or greater. The authors analyzed the costs resulting from the increased movement of allografts related to this new policy. Using a sample of nine organ procurement organizations, representing 17% of the US population and 19% of the deceased donors in 2013, data were obtained on import and export costs before Share 35 implementation (June 15, 2012, to June 14, 2013) and after Share 35 implementation (June 15, 2013, to June 14, 2014). Results showed that liver import rates increased 42%, with an increased cost of 51%, while export rates increased 112%, with an increased cost of 127%. When the costs of importing and exporting allografts were combined, the total change in costs for all nine organ procurement organizations was $11 011 321 after Share 35 implementation. Extrapolating these costs nationally resulted in an increased yearly cost of $68 820 756 by population or $55 056 605 by number of organ donors. Any alternative allocation proposal needs to account for the financial implications to the transplant infrastructure. Abstract : In a review to analyze cost changes associated with the implementation of the Share 35 organ allocation policy, the authors show an association of the policy change with an increase in imports, exports, and total cost, with a substantial impact on national costs. See article by Halazun et al onpage 137 .